A compact design of four-port high-gain MIMO antenna using hybrid coupler and dual-polarized radiators - Phuong Kim-Thi; Thang Nguyen-Van; Dat Nguyen-Tien; Tung Bui-Thanh (PLoS ONE, 2025)
This paper introduces a design methodology for a multiple-input multiple-output (MIMO) antenna that achieves multi-port operation, high gain, as well as compact dimensions. The proposed design employs two dual-polarized radiators integrated with two hybrid couplers. This architecture enables a four-port MIMO array to be realized using only two radiating elements. Meanwhile, the hybrid couplers simultaneously excite both ports of the dual-polarized elements with equal magnitude and a 90 ∘ phase difference, facilitating high-gain radiation. To validate the proposed concept, an antenna prototype was fabricated and tested. Measurements confirm that the antenna, with an overall compact size of 0.96 λ × 0.77 λ × 0.04 λ , achieves a 3.1% operating bandwidth (4.72-4.87 GHz) with inter-port isolation better than 10 dB. Within this band, the antenna maintains a measured gain of around 8.0 dBi. Additionally, the antenna also performs good diversity performance in terms of Envelop Correlation Coefficient, Diversity Gain, Channel Capacity Loss, and Mean Effective Gain.